LOXL1 deficiency in the lamina cribrosa as candidate susceptibility factor for a pseudoexfoliation-specific risk of glaucoma - Schlötzer-Schrehardt, Ursula; Hammer, Christian; Krysta, Anita W.; Hofmann-Rummelt, Carmen; Pasutto, Francesca; Sasaki, Takako; Kruse, Friedrich; Zenkel, Matthias (Ophthalmology, 2012)
To test the hypothesis that a primary disturbance in lysyl oxidase-like 1 (LOXL1) and elastin metabolism in the lamina cribrosa of eyes with pseudoexfoliation syndrome constitutes an independent risk factor for glaucoma development and progression.Observational, consecutive case series.Posterior segment tissues obtained from 37 donors with early and late stages of pseudoexfoliation syndrome without glaucoma, 37 normal age-matched control subjects, 5 eyes with pseudoexfoliation-associated open-angle glaucoma, and 5 eyes with primary open-angle glaucoma (POAG).Protein and mRNA expression of major elastic fiber components (elastin, fibrillin-1, fibulin-4), collagens (types I, III, and IV), and lysyl oxidase crosslinking enzymes (LOX, LOXL1, LOXL2) were assessed in situ by quantitative real-time polymerase chain reaction, (immuno)histochemistry, and light and electron microscopy. Lysyl oxidase-dependent elastin fiber assembly was assessed by primary optic nerve head astrocytes in vitro.Expression levels of elastic proteins, collagens, and lysyl oxidases in the lamina cribrosa.Lysyl oxidase-like 1 proved to be the major lysyl oxidase isoform in the normal lamina cribrosa in association with a complex elastic fiber network. Compared with normal and POAG specimens, lamina cribrosa tissues obtained from early and late stages of pseudoexfoliation syndrome without and with glaucoma consistently revealed a significant coordinated downregulation of LOXL1 and elastic fiber constituents on mRNA and protein level. In contrast, expression levels of collagens and other lysyl oxidase isoforms were not affected. Dysregulated expression of LOXL1 and elastic proteins was associated with pronounced (ultra)structural alterations of the elastic fiber network in the laminar beams of pseudoexfoliation syndrome eyes. Inhibition of LOXL1 interfered with elastic fiber assembly by optic nerve head astrocytes in vitro.The findings provide evidence for a pseudoexfoliation-specific elastinopathy of the lamina cribrosa resulting from a primary disturbance in LOXL1 regulation and elastic fiber homeostasis, possibly rendering pseudoexfoliation syndrome eyes more vulnerable to pressure-induced optic nerve damage and glaucoma development and progression.
EVALuna2:1645